Characterization of mechanical properties of hydroxyapatite–silicon–multi walled carbon nano tubes composite coatings synthesized by EPD on NiTi alloys for biomedical application. (June 2016) - Khalili, Vida; Khalil-Allafi, Jafar; Sengstock, Christina; Motemani, Yahya; Paulsen, Alexander; Frenzel, Jan; Eggeler, Gunther; Köller, Manfred
Abstract: Release of Ni 1+ ions from NiTi alloy into tissue environment, biological response on the surface of NiTi and the allergic reaction of atopic people towards Ni are challengeable issues for biomedical application. In this study, composite coatings of hydroxyapatite–silicon multi walled carbon nano-tubes with 20 wt% Silicon and 1 wt% multi walled carbon nano-tubes of HA were deposited on a NiTi substrate using electrophoretic methods. The SEM images of coated samples exhibit a continuous and compact morphology for hydroxyapatite–silicon and hydroxyapatite–silicon–multi walled carbon nano-tubes coatings. Nano-indentation analysis on different locations of coatings represents the highest elastic modulus (45.8 GPa) for HA–Si–MWCNTs which is between the elastic modulus of NiTi substrate (66.5 GPa) and bone tissue (≈30 GPa). This results in decrease of stress gradient on coating–substrate–bone interfaces during performance. The results of nano-scratch analysis show the highest critical distance of delamination (2.5 mm) and normal load before failure (837 mN) as well as highest critical contact pressure for hydroxyapatite–silicon–multi walled carbon nano-tubes coating. The cell culture results show that human mesenchymal stem cells are able to adhere and proliferate on the pure hydroxyapatite and composite coatings. The presence of both silicon and multi walled carbon nano-tubes (CS3) in the hydroxyapatite coating induce more adherence of viable human mesenchymal stem cells in contrast to the HA coated samples with only silicon (CS2). These results make hydroxyapatite–silicon–multi walled carbon nano-tubes a promising composite coating for future bone implant application. Graphical abstract: Highlights: HA–Si–MWCNTs coating was fabricated on NiTi implant using electrophoretic deposition. HA–Si–MWCNTs coating has highest normal load before failure during scratch test. HA–Si–MWCNTs coating shows elastic modulus of 45.8 GPa between NiTi and bone tissue. Presence of both Si and MWCNTs in HA coating induce more adherence of viable hMSCs.